Long-Term Results of Autologous Auricular Cartilage Graft Applied in Anophthalmic Orbits Unable to Wear Prosthesis - Yi-Lin Liao; Shu-Ya Wu; Yueh-Ju Tsai (Journal of Ophthalmology)
In anophthalmic patients, shallow lower fornices make wearing ocular prostheses impossible and maintaining normal social activities difficult. This study retrospectively investigated the long-term surgical outcomes of autologous auricular cartilage grafting for contracted orbits. From 1995 to 2013, 29 anophthalmic contracture sockets with inadequate lower fornices and poor prosthesis retention presented to Chang Gung Memorial Hospital in Linkou, Taiwan, were treated using this surgical method. The success rate, aesthetic outcome, recurrence, and complications were analyzed. Among the 29 patients, 15 were women, 14 were men, their mean age was 45 years, and the mean follow-up time was 52 months (range = 6–159 months). Satisfactory lid position was achieved in 25 cases (86%), and lower fornix retraction recurred in four cases (14%). Neither donor site morbidity nor auricular deformity was noted during the follow-up period. Therefore, an auricular cartilage graft can be used successfully as a compatible spacer for anophthalmic patients with shallow lower fornices and prosthesis-fitting problems in long-term follow-up.